DAMPAK PERALIHAN KEBIJAKAN PERIZINAN USAHA TAMBANG GALIAN C DI KABUPATEN INDRAMAYU - Rasji Rasji (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
Excavated material C is part of Indonesia's abundant natural resources. Its utilization is used for the greatest prosperity of the people. Excavation mining C is required to obtain a mining business permit, but many entrepreneurs in the Indramayu Regency do not have a mining business permit. On the other hand, there has been a shift in the mining permit policy for excavation C. The problem is what is the impact of the policy shift on the issue of licensing for mining mining C in Indramayu Regency? Through empirical legal research, the research results show that initially the mining business licensing policy in the Indramayu Regency was the authority of the Indramayu Regency Government. Since 2017, the mining business licensing policy for C excavation located in Indramayu Regency has changed to the authority of the West Java Provincial Government. This has an impact on the procedure for obtaining a mining business permit for C-mining, which is getting longer and more difficult, the cost of obtaining a C-mining business permit is getting bigger, C-mining activities are increasingly without a permit, and the Indramayu Regency Government does not have the authority to regulate C-excavation mining activities. unlicensed.